Kinetics of Phosphorus Uptake through Roots of Habanero Pepper (Capsicum chinense Jacq. cv. Mayapán) - Carmen Yam-Chimal; Luis Ramírez-y-Avilés; Jorge Navarro-Alberto; Francisco Solorio-Sánchez; Eduardo Villanueva-Couoh; José Noh-Medina (Agriculture, 2022)
The application of enzymatic kinetics theory on the nutrition of horticultural species is scarce. Imax and Km describe the kinetics of nutrient absorption by the plant. Imax and Km are necessary to predict phosphorus (P) uptake from soil using mathematical models, and their estimation gives information about the efficient use of P in plants. Imax and Km for habanero pepper (Capsicum chinense Jacq. cv. Mayapán) were determined using the modified exhaustion method. Depletion of P by the roots was obtained with 0.01, 0.125, 0.25, 0.50, and 1.00 mM P L−1. P-depletion data over time were fitted to an exponential-regression model to obtain the initial P-uptake rates by the roots. Initial P-uptake rates were significantly different (p < 0.001) depending on the levels of P in the solution. Imax and Km were predicted by iteratively fitting the initial P-absorption rates in terms of the concentration of P to the Michaelis–Menten model. The average Imax was 3.49 × 10−7 mM cm2 s−1 and Km was 2.59 × 10−2 mM P L−1. These results show that the habanero pepper root can uptake 1.08 × 10−5 mg P L−1 per cm2 in the soil solution per second and P transporters are saturated with 2.59 × 10−2 mM P L−1.